ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL TENTANG PEMUAIAN DI SMP KEMALA BHAYANGKARI - Anggriani, Teti; Tandililing, Edy; Syukran, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe research aims to analyze the kinds of student’s error, to calculate the percentage of student errors and to find the cause of the student's error in resolving the problem of expansion. The form of research is descriptive research. The samples in this research were 41 students in VII grade in SMP Kemala Bhayangkari. The Instrument to Collect data in this research is an essay test and interview. The analysis data techniques using the Miles and Huberman model. The results of this research were 3.52% of students experienced concept error, 15.04% of students experienced errors in writing symbols, 20.73% of students experienced calculate errors and 33.74% of students experienced unit errors. The cause of the student's error is that students experience misconceptions, forget, inadvertence, difficult to counting on numbers that have multiple numbers behind a comma, do not know how to convert the right unit and unit to the answer. Based on the explanation of student of the causes of student errors in resolving the problem, it is hoped that it will be the base for the teachers and the next researchers to improve student learning outcomes especially in grade VII on the expansion lesson. Keywords: Cause of Error, Descriptive Research, Kinds of error, Percentage of error, Problem of Expansion,